Analisis Pendekatan Pembelajaran Edukatif dalam Meningkatkan Literasi Digital pada Siswa Sekolah Dasar - Mohammad Hayyi; Nuril Huda; Victor Maruli Tua L. Tobing (Jurnal Penelitian Pendidikan IPA, 2025)
The use of digital technology has brought about major changes in the world of education, especially at the elementary school level. However, the use of gadgets in an educational manner requires proper guidance. In this context, the role of parents is very important. Unfortunately, unequal access to technology and limited teacher capabilities are the main obstacles in the development of digital literacy, especially in rural areas. This study aims to examine the influence of the role of parents, cultural capital, and social capital on the educational digital literacy of elementary school students in Madura. The method used is quantitative descriptive with a survey of 200 parents. Data collection was carried out through online and direct questionnaires, then analyzed using SEM-PLS 3.0 and a Likert scale. The results of the study indicate that parental involvement and social capital significantly influence students' digital literacy, highlighting the importance of collaboration between parents, teachers, and the school environment in supporting elementary school students' digital literacy skills. Meanwhile, cultural capital did not significantly impact elementary school students' digital literacy.